Physiological characteristics of international female soccer players - Manson, S. A.; Brughelli, M.; Harris, N. K. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate the physiological characteristics of Fédération Internationale de Football Association (FIFA) eligible international female soccer players aged 14-36 years and to determine if measures were significantly different for players selected (i.e., starters) to the starting line up for an FIFA tournament as compared with those not selected (i.e., nonstarters). Fifty-one (N = 18 Under 17; N = 18 Under 20; N = 15 Senior) international female soccer players participated in this study. The subjects underwent measurements of anthropometry (height and body mass), lower body strength (isokinetic testing), sprint kinetics and kinematics (nonmotorized treadmill), leg power (unilateral jumping), and maximal aerobic velocity (30:15 intermittent fitness test) during the final preparatory stage for an FIFA event. Outcomes of the age group data indicate that differences in physiological capacities are evident for the Under 17 players as compared with those for the Under 20 and Senior capped international players, suggesting a plateau in the acquisition of physical qualities as players mature. Starters tended to be faster (effect size [ES] = 0.55-1.0, p < 0.05) and have a higher maximal aerobic velocity (ES = 0.78-2.45, p < 0.05), along with greater eccentric leg strength (ES = 0.33-1.67, p < 0.05). Significant differences were detected between starters and nonstarters for isokinetic leg strength (ES = 0.54-1.24, p < 0.05) and maximal aerobic velocity (ES = 0.87, p < 0.05) for Under 17 players, where maximal aerobic velocity was the primary difference between starters and nonstarters (ES = 0.83-2.45, p < 0.05) for the Under 20 and Senior players. Coaches should emphasize the development of speed, maximal aerobic velocity, and leg strength in developing female soccer players.